Short‐Term Effects of Atorvastatin in Normal Dogs and Dogs with Congestive Heart Failure Due to Myxomatous Mitral Valve Disease. (12th June 2013) - Cunningham, S.M.; Rush, J.E.; Freeman, L.M.
<x xml:space="preserve">Abstract</x> Background 3‐Hydroxy‐3‐methylglutaryl coenzyme A reductase inhibitors (statins) may improve heart failure class and survival in people with congestive heart failure (CHF) of various etiologies. Hypothesis/Objectives To evaluate the tolerability of atorvastatin in healthy dogs, and the short‐term effects of atorvastatin on clinical markers of disease severity, lipid profiles, and markers of systemic inflammation and oxidative stress in dogs with CHF. Animals Eleven normal dogs and 12 client‐owned animals with CHF attributable to myxomatous mitral valve disease. Methods Prospective nonblinded observational study. Normal dogs (n = 11) were first treated with atorvastatin and re‐evaluated after 14 and 30 days for clinical tolerability and alterations in certain laboratory results. Subsequently, dogs with CHF (n = 12) were treated with atorvastatin at a dosage of 2 mg/kg q24h for 8 weeks. Echocardiography, blood pressure (BP), quality of life questionnaire, and blood sampling were performed pre and post atorvastatin administration. Results Atorvastatin was well tolerated and did not result in apparent adverse effects or biochemical abnormalities in healthy dogs and in dogs with CHF. Healthy dogs experienced a decrease in total cholesterol (TC) concentration (P = .03) after atorvastatin administration. Decreases in TC concentration (P = .02), non‐HDL cholesterol concentration (P = .02), total white blood cell count (P = .03), neutrophils (P = .01), and systolic BP (P = .01) were noted in the CHF group after 8 weeks of atorvastatin. Conclusions and Clinical Importance Atorvastatin was well tolerated at clinically relevant doses in healthy dogs and dogs with CHF. Further investigation into the effects of statin treatment in dogs with CHF is warranted.